Association of Interleukin-12 and Interleukin-18 Polymorphisms with Acute Lymphoblastic Leukemia Disease in Iraqi Patients - Hasan, Lafaw O.; Rasheed, Taban K. (Iraqi Journal of Science, 2024)
Acute lymphoblastic leukemia (ALL) is a blood cancer where high numbers of abnormal, immature lymphocytes called blasts start over-multiplying in the bone marrow. The lymphocyte cells and interleukins are crucial for controlling the immune response in tumor microenvironment. Many of the single nucleotide polymorphisms (SNPs) of some interleukin genes may change protein synthesis or function and regulate the immune response. A lot of these changes have been connected to a high risk of developing cancer. Aim of this study was to investigate the potential association between IL-12 (+1188 A/C) (rs3212227) and IL-18 (–607 A/C) (rs1946518) polymorphism with serum levels of interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α) and their genotypes association with the susceptibility to ALL disease in Iraqi patients. The study included 59 ALL patients and 30 healthy controls. The detection of IL-12 and IL-18 SNP genes was determined by ARMS-PCR methods and serum levels of IFN-γ and TNF-α were determined by utilizing enzyme linked immuno-sorbent assay (ELISA) kits. Results observed no significant association of IL-12 and IL-18 polymorphism with serum IFN-γ and TNF-α level. Genotyping frequencies of IL-12 (+1188A/C) CA, AA and CA+AA genotypes showed a strong association with the development of ALL disease, IL-18 genotypes showed no significant association with the disease progression.